TikTok Live Streaming Strategy for Msmes in Tasikmalaya to Increase Sales - Pertiwi, Hani; Maesaroh, Syti Sarah (Journal of Investment Development, Economics and Accounting, 2024)
This research aims to analyze and supplement the live streaming strategies that have not yet been implemented at Lalada Food. Additionally, this study evaluates the impact of the closure and reopening of TikTok Shop on live streaming strategies and proposes new strategies to increase sales and address the challenges arising from these changes. This research uses a qualitative approach focusing on in-depth observation. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats faced by Lalada Food in conducting live streaming. The company occupies a position in quadrant II of the SWOT analysis, which represents a situation where the company’s strengths are greater than its weaknesses, but opportunities are smaller than threats. Therefore, the company is in a strong position but faces significant challenges. The strategy used in this quadrant is the diversification strategy. This research is the first to analyze the implementation of live streaming strategies following the closure and reopening of TikTok Shop. This study provides new insights into their marketing strategies through live streaming to increase sales and address business challenges